DIGITAL TRANSFORMATION AND STRATEGIC GOVERNANCE IN HIGHER EDUCATION: CONCEPTUAL INTEGRATION FRAMEWORK FOR EMERGING ECONOMIES (Eureka Journal of Business, Economics & Innovation Studies, 2026)
The digitalization of higher education has accelerated rapidly in the last decade, reshaping academic governance, teaching practices, and institutional management. Universities increasingly rely on digital platforms, data-driven decision systems, and technology-enhanced learning models to remain competitive in the global knowledge economy. Despite these advancements, institutions in emerging economies face structural barriers that hinder the effective integration of digital transformation with strategic governance.This study examines the relationship between digital transformation and strategic governance in higher education institutions within emerging economies. The paper proposes a conceptual model linking institutional leadership, digital infrastructure, policy governance, and digital skills to institutional digital transformation outcomes. The research further introduces hypotheses and an empirical regression framework that can be applied in future quantitative studies. The findings highlight the importance of governance coordination and technological capacity in strengthening university performance in the digital era.
Keywords: Digital transformation; higher education governance; digital university; emerging economies; educational innovation; digital policy.